A Comparative Study of Organizational Role Stress and Organizational Commitment Among The University Faculty Members of India and Saudi Arabia - Qazi, Sayeeduzzafar; Nazneen, Afroze (European Scientific Journal, ESJ, 2016)
Stress is define as a dynamic condition in which an individual is confronted with an opportunity , constraint , demand related to what he or she desires and for which the outcome is perceived to be both uncertain and important. Organizational role stress comes from three sectors i.e. job and organization, social factor and intra-psychic factor. Organizational commitment is defined as â€œan individual psychological bond to the organization, including a sense of job involvement, loyalty and belief in the values of the organizationâ€. The cross cultural study was conducted on 245 Faculty members working in various Indian and Saudi Arabian universities using questionnaire method and standardized psychometric tests were used to collect the data on the variable under investigation. The study reveals that faculty members of Saudi Arabia were shown moderate level of organizational role stress and low level of organizational commitment while their Indian counterparts were shown high level of organizational role stress and moderate level of organizational commitment. The organizational role stress dimensions were found to be negatively correlated with organizational commitment means if the organizational role stress will go up the commitment level of the faculty members will go down and affect the performance of the faculty members negatively. The data were also analyzed using other demographic variables and the obtained results were discussed.